PLAYING SIMPLE GRAMMAR GAME AS AN ALTERNATIVE WAY TO HELP PRIMARY SCHOOL STUDENTS IMPROVE THEIR GRAMMAR - Hendrikus Male (Jurnal Dinamika Pendidikan, 2017)
ABSTRACTThis paper explores the teaching of grammar to foreign young learners. It is aimed at giving some insight to teachers specifically to private English teachers encompassing primary young learner, simple grammar game, and teaching grammar to young learner. This article also provides information of how to conduct simple grammar game in EFL class. Although it is still debatable concerning the teaching of grammar to young learners, teachers should provide fun and interesting activities to teaching it to their pupils. Therefore, it is crucial as the English teacher in teaching grammar to young learners in order to help them recognize adequate number of basic knowledge or language skills in their level. In order to bridge the gap, simple grammar game could be used as a natural way to help and lead them to the understanding of the grammar that they may put and make use of it into their real life context in learning English.Keywords: Grammar, Primary Young Learners, Language Skills ABSTRAKMakalah ini membahas pengajaran tatabahasa Inggris kepada anak-anak Sekolah Dasar dengan tujuan untuk memberikan masukan kepada para guru khususnya untuk guru bahasa Inggris yang mencakupanak-anak Sekolah Dasar, permainan tatabahasa sederhana, dan tata bahasa pengajaran dalam anak-anak Sekolah Dasar. Artikel inijuga memberikan informasi bagaimana cara menjalankan permainan tatabahasa sederhana di kelas bahasa Inggris. Meski masih bisa diperdebatkan mengenai pengajaran tatabahasa kepada anak-anak Sekolah Dasar, guru diharapkan untuk memberikan kegiatan yang menyenangkan dan menarik untuk mengajarkannya kepada murid-muridnya. Oleh karena itu, sangat penting bagi guru bahasa Inggris dalam mengajarkan tatabahasa kepada anak-anak Sekolah Dasar sehingga membantu siswa/i dalam mengenali pengetahuan dasar atau kemampuan bahasa yang memadai ditingkat mereka. Untuk menjembatani kesenjangan tersebut, permainan tatabahasa dapat digunakan sebagai salah satu cara alami untuk membantu dan mengarahkan anak-anak Sekolah Dasar dalam memahami tata bahasa yang mungkin dapat dimasukkan dan gunakan ke dalam konteks kehidupan nyata mereka dalam mempelajari bahasa Inggris.Kata Kunci: Permainan Tatabahasa, anak-anak Sekolah Dasar,Pengetahuan Dasar